280 + (-22) equals 258.
280 + (-22)
5 answers
280 + (-2t)
(T = 20)
(T = 20)
To solve the expression \(280 + (-2t)\) with \(t = 20\):
-
Replace \(t\) with 20: \[ 280 + (-2 \cdot 20) \]
-
Calculate \(-2 \cdot 20\): \[ -2 \cdot 20 = -40 \]
-
Now substitute that back into the expression: \[ 280 + (-40) \]
-
Finally, calculate: \[ 280 - 40 = 240 \]
So, \(280 + (-2t)\) when \(t = 20\) equals \(240\).
280 + (-2t)
(T = 4)
(T = 4)
To solve the expression \(280 + (-2t)\) with \(t = 4\):
-
Substitute \(t\) with \(4\): \[ 280 + (-2 \cdot 4) \]
-
Calculate \(-2 \cdot 4\): \[ -2 \cdot 4 = -8 \]
-
Now substitute that back into the expression: \[ 280 + (-8) \]
-
Finally, calculate: \[ 280 - 8 = 272 \]
So, \(280 + (-2t)\) when \(t = 4\) equals \(272\).